Optimization of the G&H Bubble Model - Thomas L. Geers; Chung-Kyu Park (Shock and Vibration)
A spherical model for the bubble created by an underwater explosion is enhanced to account, in approximate fashion, for the effect of bubble distortion on translation and dilation. The enhancement consists of introducing artificial drag in the form C|v|P , where ν is translation velocity, and C, P produce an optimum fit to empirical formulas for the second dilation maximum and first two translation jumps. The recommended values are C = 0.4 and P = 1 for charge weights between 100 lb–1000 lb and and depths exceeding 200 ft.